Utilization and Effectiveness of Grade-Separated Pedestrian Crossings: A Case Study of Kathmandu - Dhakal, Binaya Prasad; Shrestha, Gaurab; Panta, Ishwor; Panth, Gaurav (Journal of Advanced College of Engineering and Management, 2026)
This study examines the utilization and effectiveness of grade-separated pedestrian crossings in underdeveloped urban settings, focusing on Kathmandu. Observations of 47,783 pedestrian crossings across five sites (four overhead bridges and one underpass) were conducted over 15 days, collecting data on age, gender, and crossing functionality using manual and video methods. The analysis revealed a high overall utilization rate of 83.20%. The underpass had the highest usage at 97.92%, compared to 93.67% for overhead bridges. Age and gender significantly influenced usage patterns, with individuals under 25 and males utilizing crossings more frequently. Site selection considered factors such as lane count, median barriers, and facility type, highlighting their impact on utilization. Median barriers and the ergonomic design of facilities, particularly the number of steps, emerged as key determinants of utility. The findings underscore the importance of strategic planning and design in enhancing pedestrian safety and usability in underdeveloped urban areas. Median barriers and ergonomic considerations, such as minimizing physical effort, play a pivotal role in encouraging usage. This research provides valuable insights for urban planners and policymakers to develop pedestrian-friendly infrastructure, addressing safety concerns and demographic needs in similar urban contexts.